Answers

2014-10-20T21:50:27+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
9t² - 6t + 1 = 0
⇒ 9t² - 3t - 3t + 1 = 0
⇒ 3t(3t-1) -1(3t-1) = 0
⇒ (3t-1)(3t-1)=0
⇒ (3t-1)² = 0
So both roots are same
⇒ 3t = 1
⇒ t = 1/3

Verification of relationships:
Sum of roots = (1/3)+(1/3) = 2/3 = -(-6)/9 = -b/a
Product of roots = (1/3)*(1/3) = 1/9 = c/a

0
2014-10-20T23:56:27+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
9 t² - 6 t + 1 = 0 
  t² - 2/3 t + 1/9 = 0
    (t - 1/3)² = 0          t = 1/3 is a double root of the polynomial.

Verification of the relationship:
 
           roots of  ax² + b x + c = 0  are    x = (-b+- √(b²-4ac) ) / 2 a

                     b = -6  a = 9  c = 1

     zeros = roots  = (6 + - √(6²-4*9) )/18 = (6 +- 0) / 18 = 1/3   so verified.

0